IMPLEMENTASI TERKAIT KESIAPAN PETUGAS PANTI TERHADAP SISTEM PENANGGULANGAN GAWAT DARURAT TERPADU (SPGDT) DI PANTI SOSIAL LANJUT USIA HARAPAN KITA PALEMBANG - TRILIA WM (Masker Medika, 2024)
Background: The Integrated Emergency Management System (SPGDT) is one of the health service innovations to handle emergency cases at the Harapan Kita Social Institution for the Elderly, Palembang. Residents of the orphanage still have complaints about the implementation of the SPGDT program, complaints are slow to handle, call center access is not easy to contact, the role of case management by the orphanage staff team is still slow. Purpose: to analyze the implementation related to the readiness of the nursing home staff regarding the integrated emergency response system (SPGDT). Methods: qualitative research with in-depth interviews and observation. There were 3 informants in the study consisting of the head of the orphanage, staff and employees at the Harapan Kita Palembang Social Home for the Elderly. The variables used to see the implementation of the readiness of the orphanage officers are communication, resources and infrastructure. The research was carried out for 3 months February-April 2023. Data analysis was processed according to the characteristics of content analysis, namely: data collection, data reduction, verification, data presentation and drawing conclusions. Research results: shows that the implementation related to the readiness of the orphanage staff has not gone as expected, efforts to increase knowledge and access have not been achieved, communication and coordination between teams have not been effective. Conclusion: the integrated emergency management system at Harapan Kita Social Institution Palembang is still not optimal and has not been supported by medical personnel and adequate infrastructure